STUDENTS’ PERCEPTION TOWARD SPADA UPGRIS AS DIGITAL PLATFORM IN LEARNING PROCESS - Entika Fani Prastikawati; Asropah Asropah (Universitas Muria Kudus, 2020)
This research is trying to figure out the students’ perceptions and difficulties arise in the application of SPADA (Sistem Pembelajaran Daring) UPGRIS. The method used in this research is descriptive qualitative research. There are 150 Indonesian students of the third semester in Universitas PGRI Semarang as the sample of the study. Those samples come from five different majors, namely English education department, Indonesian language education department, management department, engineering,department and law department of Universitas PGRI Semarang (UPGRIS). It is based on the fact that the third-semester students had joined SPADA UPGRIS platform as it was required by the lecturers. The finding shows that most students have positive feelings and perceptions of the application of SPADA UPGRIS. They consider SPADA UPGRIS as a new experience in learning which gains their capability in technology competence. On the other hand, some difficulties were faced by the students such as personal internet connection, less communication with friends, material file size provided, and inability in using a computer.